Benthic community structure, diversity, and productivity in the shallow Barents Sea bank (Svalbard Bank) - Kędra, Monika (Springer-Verlag, 2012)
The Barents Sea is among the most productive areas in the world oceans, and its shallow banks exhibit particularly high rates of primary productivity reaching over 300 g C m(−2)year(−1). Our study focused on the Svalbard Bank, an important feeding area for fishes and whales. In order to investigate how benthic community structure and benthic secondary production vary across environmental gradients and through time, we sampled across the bank and compared results with a similar study conducted 85 years ago. Considerable variability in community structure and function across bank corresponded with differences in the physical structure of the habitat, including currents, sedimentation regimes and sediment type, and overlying water masses. Despite an intensive scallop fishery and climatic shifts that have taken place since the last survey in the 1920s, benthic community structure was very similar to that from the previous survey, suggesting strong system resilience. Primary and secondary production over shallow banks plays a large role in the Barents Sea and may act as a carbon subsidy to surrounding fish populations, of which many are of commercial importance.